Patterns Of Road Traffic Accident At Emergency Department Of Patan Hospital - Shrestha, Sitaram (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Introduction: Road traffic injuries are a major cause of death and disability globally.1, 2 Road traffic injuries kill about 3000 people and 30000 are injured and disabled for life every day.3 Road traffic injuries are currently ranked ninth globally, and the ranking is projected to rise to third by 2020.4In fact, road traffic injuries alone ranked as the number one cause of the burden of disease among children between 5-14 years in 2000.5 .Report from WHO says fifty percent of the injuries occurred in the 15-44 years age group with the male to female ratio 3:1.6 In Nepal, as per estimates of morbidity and mortality for 1988-1999, injury contributed 9% to total mortality.7 Road traffic injures in developing counties mostly affect pedestrians, pass-engers and cyclists.8 The reasons for the high burden of road traffic injuries in developing countries are: growth in the numbers of motor vehicles; poor enforcement of traffic safety regulations; .8 This study was done to evaluate the pattern of Road traffic accident, visited in Emergency department Patan Hospital. Methods: This is a prospective and descriptive study which was done at Patan Hospital. All casualties presented to Emergency department due to RTA were included in Study. Results: Most common vehicle involved in Injury was Motorcycle and Microbus. Male population was most affected and most vulnerable age falls on 11-30 years of age. Conclusion: Road traffic accidents are increasing and it mainly affects to young and adult age groups. Effective measures need to implement to minimize road traffic accidents